A Road to “Unity in Diversity”: The Case of Indonesia’s Chinese Minority Group - Ignasius Loyola Adhi Bhaskara (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2023)
Indonesia is well-known for its diverse ethnic groups. The lovely motto bhinneka tunggal ika (unity in diversity) has long been used to foster national identity and demonstrate how these many ethnic populations may cohabit peacefully. However, this is not always the case, especially among the Chinese-Indonesian community. This article examines the history and current situation of the Chinese-Indonesian minority, which has faced various forms of violence and discrimination since the Dutch colonial era, to understand why Chinese Indonesians are frequently used as a scapegoat for problems in the country, particularly those related to economic disparity. It explores the causes and implications of the unfavourable sentiment against this ethnic group using Johan Galtung's concepts of direct, structural, and cultural violence. It also evaluates the Indonesian government's legislative and social actions to solve the issue, concluding that they are insufficient to promote constructive peace and justice. The article argues that a genuine reconciliation process is required to heal the trauma and promote mutual understanding among Chinese Indonesians and other ethnic groups.